Oral hygiene practices and knowledge among children of age 10-13 years in a private school in Chennai, South India - Kanagavelu, Aravind Sunderavel Kumaravel; Chandran, Arun; Brinda, Jaya (International Journal Of Community Medicine And Public Health, 2020)
Background: Oral health is an important and proven determinant of overall health and quality of life. It is well established that oral health and non-communicable diseases share common risk factors. Our study was designed to assess the practice and knowledge of oral health among 10-13 years old because at this age, lifelong beliefs and essential skills are developed. Methods: A cross-sectional study was done by randomly selecting students from V to VIII standards in a private school. Data was collected using a pre-designed questionnaire. The results were analysed using ‘Jamovi’ software with ’Pearson Chi-square test’ and a p-value of less than 0.05 was considered statistically significant. Results: Out of the 210 students, only around 1/3rd of the students used both brush with toothpaste, and dental floss to clean their teeth. 123 (58.6%) students brushed twice a day. The association between the frequency of brushing and the age groups was statistically significant. Gender played a role in the duration of brushing. Conclusions: It can be noted from our study that the oral practices and knowledge was better in 10-11 years olds than the 12-13-year olds and better in girls than in boys. Thus, oral education must be tailor made based on the calibre of a particular group instead of ‘one for all’ method.